Persepsi Mahasiswa Calon Pendidik terhadap Pembelajaran Daring Berbasis ICT pada Masa Pandemik Covid-19 - Ratni Purwasih; Komala; Fifiet Dwi Tresna Santana (Edumatica : Jurnal Pendidikan Matematika, 2020)
The Covid-19 outbreak provides opportunities in the field of education, especially learning on campus, to learn online. Online learning in the era of the industrial revolution 4.0 is a form of implementation to adapt to the rapid development of ICT. Through online learning, lecturers and students are not bound by time and space to interact with the learning process. Online learning makes use of independent teaching materials that can be accessed by anyone at any time via internet technology. Online learning will facilitate the improvement and storage of lecture materials so that updating of electronic teaching materials is easy. The purpose of this study was to describe the perceptions of ICT-based online learning among prospective educators. The research sample was 270 students of the IKIP Siliwangi. The data collection technique uses google from which consists of 10 statements. The findings in this study are students like face-to-face lectures compared to online learning, the online media that students like are cellphones, the preferred online place to study is home, the online application used by lecturers is google classroom, lecture materials are delivered by lecturers in the form of assignments. online assignments and lectures make students less understanding of course material. The obstacles experienced during online lectures include pedagogical, technologi and didactic obstacles.